The interaction between uric acid and high-density lipoprotein cholesterol on the prognosis of patients with acute myocardial infarction - Yang, Yu; Zhang, Jian; Jia, Lin; Su, Jiannan; Ma, Mengqing; Lin, Xianhe (Frontiers in Cardiovascular Medicine, 2023)
Background: The significance of uric acid (UA) and high-density lipoprotein cholesterol (HDL-C) in the prognosis of acute myocardial infarction (AMI) remains controversial. This study investigated the effect of interaction between UA and HDL-C on the prognosis of patients with AMI. Methods: In total, 480 patients with AMI were included in this study. Baseline and follow-up data were collected, and the primary endpoint was major adverse cardiovascular events (MACE). The secondary endpoint was all-cause death. Both additive and multiplicative interactions were calculated to evaluate their interaction with prognosis. Then, the impact of UA and HDL-C ratio (UHR) on prognosis was assessed. Results: Over a median follow-up period of 41 (30,46) months, 136 (28.3%) MACEs, and 44 (9.2%) mortality rates were recorded. There was a positive additive interaction between UA and HDL-C for MACEs. The attributable proportion (AP) showed that 46% of the estimated effect (MACE in patients) was attributable to this interaction. The synergy index (SI) was 2.04 (1.07,3.88) for MACE, indicating that the risk for patients presenting with both risk factors was greater than the sum of the risk factors alone. Multivariate Cox regression analysis revealed that UHR independently predicted MACEs and mortality. Kaplan–Meier survival curves according to tertiles of UHR showed statistically significant differences in MACE (log-rank test, P<0.001). Receiver operating characteristic (ROC) analysis showed that the area under the curve (AUC) of UHR for predicting MACE was 0.716. Conclusion: The coexistence of high UA and low HDL-C has a synergistic effect and provides further information for risk stratification of patients with AMI.UHR is a simple and easily available prognostic indicator independent of traditional risk factors.